3(3+1)=(9-2x)

Simple and best practice solution for 3(3+1)=(9-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3+1)=(9-2x) equation:


Simplifying
3(3 + 1) = (9 + -2x)

Combine like terms: 3 + 1 = 4
3(4) = (9 + -2x)

Multiply 3 * 4
12 = (9 + -2x)

Remove parenthesis around (9 + -2x)
12 = 9 + -2x

Solving
12 = 9 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
12 + 2x = 9 + -2x + 2x

Combine like terms: -2x + 2x = 0
12 + 2x = 9 + 0
12 + 2x = 9

Add '-12' to each side of the equation.
12 + -12 + 2x = 9 + -12

Combine like terms: 12 + -12 = 0
0 + 2x = 9 + -12
2x = 9 + -12

Combine like terms: 9 + -12 = -3
2x = -3

Divide each side by '2'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 6n=(n+5) | | 30=-8x+2(x-6) | | y=mx+bfindx | | x^1/4=2 | | 5x-15=2x+20 | | 90+3+x+x-8=180 | | 10n-0.75=0.1n-0.375 | | 2-7g=2-g | | 2e^3x-9=0 | | 12a=3a+2.5a+a | | -1=6x-31 | | 15.93+.09(x+3)=16.43-.13x | | -3(3y-7)+2(2y+8)= | | 2[-2(4x+5)+4(3x-4)]= | | z/3=11 | | 5x-7=2x-14 | | 7/3.7/5 | | 51=50 | | (x/3)-9= | | -7y-12w=29 | | (-3/7)÷(-14/11) | | -5y-8=-3y+2 | | (4y^2+2y+1)-(y^2-9)= | | 13/11-(-1/7) | | 22x+8=-80 | | -3(4y-9)+2(3y+5)= | | x/x-10=3/1 | | 1/2-(-15/8) | | -24+8a=-5(-3a-4) | | -2.6y+4=.9y-17 | | 2r-8=5r+35 | | 5x+1+x=-27 |

Equations solver categories